The longitudinal static stability of tailless aircraft - de Castro, Helena V. (Cranfield University, 2001)
This paper describes the development of a simple theory of the longitudinal controls fixed static stability of tailless aeroplanes. The classical theory, as developed for the conventional aircraft, is modified to accommodate the particular features of the tailless aeroplanes. The theory was then applied to a particular blended-wing-body tailless civil transport aircraft, BWB-98.